ETIKA PENDIDIK MENURUT IMAM AL-NAWAWI DALAM KITAB MAJMU’ SYARH AL-MUHADHDHAB DAN RELEVANSINYA DENGAN UNDANG-UNDANG NO. 14 TAHUN 2005 TENTANG GURU DAN DOSEN: Etika Pendidik - Imam Muddin (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
In carrying out the educational process, an educator must pay attention to the ethics of the educator with full awareness and responsibility. Imam al-Nawawi is one of the Islamic thinkers who pays attention to the importance of ethics for an educator. One of his thoughts on ethics is outlined in his book entitled Majmu 'Syarh Al-Muhadhdhab. In history, the book is actually a book of Fiqh which is used as a reference for scholars', but at the beginning of the book it is explained about the ethics of educators. The formulations in this study are: (1) How is the ethics of educators towards oneself in Islamic education according to Imam al-Nawawi ?, (2) How is the ethics of educators towards students in Islamic education according to Imam al-Nawawi ?, (3) What is the ethics of educators towards knowledge in Islamic education according to al-Nawawi? (4) How is the relevance of ethics of educators in Islamic education according to Imam al-Nawawi in the book Majmu 'Syarh Al-Muhadhdhab with the code of ethics of teachers in education ?. This research uses a qualitative descriptive analysis approach and the type of research is library research, with documentary techniques. The data analysis is content analysis. The conclusions of this study are (1) the ethics of educators according to Imam al-Nawawi is divided into three, namely: the ethics of educators towards themselves, towards students, and towards science, (2) the ethical thoughts of educators according to Imam al-Nawawi are relevant to the Law No. 14 of 2005 concerning Teachers and Lecturers.